Effects of mental fatigue on perception of effort and performance in national level swimmers - de Lima-Junior, Dalton; Caporaso, Giuseppe; Cortesi, Matteo; Fortes, Leonardo de Sousa; Marcora, Samuele Maria (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to investigate the effects of mental fatigue on the perceptual and physiological responses to swimming at the lactate threshold (LT) and on 400-m front-crawl performance.MethodsTen national-level swimmers were tested three separate times. In the first session, swimmers performed a 7x200-m incremental test for LT assessment. In sessions two and three, participants performed the AX-Continuous Performance Task for 90-min (mental fatigue condition) or rested for 90-min (control condition) in a randomized and counterbalanced order. After the experimental manipulation, the participants performed a 12x100-m constant-speed test at LT followed by a 400-m front-crawl performance test. Fatigue was measured using the Brunel Mood Scale before and after the experimental manipulation. Heart rate (HR), blood lactate concentration (La) and rating of perceived exertion (RPE) were measured during the swimming tests. Generalized Mixed Models were used to test main effects and interactions, and Holm-Bonferroni post-hoc correction was applied when necessary (p < 0.05).ResultsFatigue increased only for the mental fatigue condition (p = 0.018). During the 12 x 100 m constant-speed test at LT, athletes in the mental fatigue condition presented higher RPE (p = 0.001) despite similar HR and La responses compared to control. Performance in the 400-m front-crawl test was significantly impaired in mentally fatigued swimmers (p < 0.001).ConclusionThese findings show that mental fatigue increases the perception of effort during swimming at LT despite no significant physiological alterations and reduces 400-m front-crawl performance in national level swimmers.